A phase 1 study of the antibody‐drug conjugate brentuximab vedotin with re‐induction chemotherapy in patients with CD30‐expressing relapsed/refractory acute myeloid leukemia. Issue 6 (20th December 2019) - Narayan, Rupa; Blonquist, Traci M.; Emadi, Ashkan; Hasserjian, Robert P.; Burke, Meghan; Lescinskas, Christopher; Neuberg, Donna S.; Brunner, Andrew M.; Hobbs, Gabriela; Hock, Hanno; McAfee, Steven L.; Chen, Yi‐Bin; et al.
Abstract : Background: Outcomes for patients with relapsed/refractory acute myeloid leukemia (R/R AML) remain poor. Novel therapies specifically targeting AML are of high interest. Brentuximab vedotin (BV) is an antibody‐drug conjugate that is specific for human CD30. In this phase 1 dose escalation study, the authors evaluated the safety of BV combined with mitoxantrone, etoposide, and cytarabine (MEC) re‐induction chemotherapy for patients with CD30‐expressing R/R AML. Methods: Using a standard dose escalation design, the authors evaluated 3 dose levels of BV (0.9 mg/kg, 1.2 mg/kg, and 1.8 mg/kg) administered once on day 1 followed by MEC on days 3 through 7. Results: There were no dose‐limiting toxicities noted and the maximum tolerated dose was not reached. The recommended phase 2 dose of BV was determined to be 1.8 mg/kg when combined with MEC. The side effect profile was similar to that expected from MEC chemotherapy alone, with the most common grade ≥3 toxicities being febrile neutropenia, thrombocytopenia, and anemia (toxicities were graded using the National Cancer Institute Common Terminology Criteria for Adverse Events [version 4.0]). Among the 22 patients enrolled on the trial, the composite response rate was 36%, with a composite response rate of 42% noted among those who received the highest dose of BV. The median overall survival was 9.5 months, with a median disease‐free survival of 6.8 months observed among responders. Approximately 55% of patients were able to proceed with either allogeneic hematopoietic stem cell transplantation or donor lymphocyte infusion. Conclusions: The combination of BV with MEC was found to be safe in patients with CD30‐expressing R/R AML and warrants further study comparing this combination with the use of MEC alone in this population (ClinicalTrials.gov identifier NCT01830777). Lay summary: The outcomes for patients with relapsed/refractory acute myeloid leukemia (R/R AML) are exceptionally poor. New and emerging treatment combinations are actively being studied in an effort to improve outcomes. The authors examined the combination of brentuximab vedotin, an antibody product that recognizes a marker called CD30, with mitoxantrone, etoposide, and cytarabine (MEC), a common chemotherapy regimen, in patients with R/R AML that expressed the CD30 marker. The authors found that the combination was safe and well tolerated. Future studies comparing this new combination with the use of MEC alone can help to inform its effectiveness for this patient population. Abstract : In the current phase 1 study, the combination of brentuximab vedotin, an antibody‐drug conjugate targeting CD30, and re‐induction chemotherapy (mitoxantrone, etoposide, and cytarabine) was found to be safe for patients with CD30‐expressing relapsed/refractory acute myeloid leukemia. The results suggest that CD30 may be a target of further exploration in this patient population.